Comparison Development of MSME Credit in The Sumatera Region - Hamzah Hamzah; Devi Valeriani; Aning Kesuma Putri (Economics Development Analysis Journal, 2020)
The purpose of this study was to determine and analyze the development of bank credit distribution in the MSME sector in Sumatra Region. This study uses secondary data for the 2016-2018 period from the publication of Bank Indonesia and the Central Statistics Agency. The data analysis used was comparative analysis. Comparative analysis is a quantitative analysis carried out by comparing the similarities and differences based on the data and the properties of the objects discussed in a certain period. The results showed that the highest MSME sector bank lending was in North Sumatra Province, while the lowest bank credit distribution was in the MSME sector in the Sumatra Region in the Bangka Belitung Islands Province. The government needs to develop and improve credit for MSME players, so that MSMEs in Indonesia, especially in the Sumatra region, can compete and be innovative in following the development of the business world. Well-channeled UMKM credit will result in a better development of the business world because of the ease of access to capital.